Proceedings 2019 Network and Distributed System Security Symposium 2019
DOI: 10.14722/ndss.2019.23155
|View full text |Cite
|
Sign up to set email alerts
|

JavaScript Template Attacks: Automatically Inferring Host Information for Targeted Exploits

Abstract: Today, more and more web browsers and extensions provide anonymity features to hide user details. Primarily used to evade tracking by websites and advertisements, these features are also used by criminals to prevent identification. Thus, not only tracking companies but also law-enforcement agencies have an interest in finding flaws which break these anonymity features. For instance, for targeted exploitation using zero days, it is essential to have as much information about the target as possible. A failed exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Sanchez-Rola et al [50] showed a method relying on computer internal clock imperfections to fingerprint unique machines. Schwarz et al [51] presented JavaScript template attacks to create fingerprints and retrieved the instruction-set architecture and the used memory allocator.…”
Section: Hardware-based Side-channel Attacksmentioning
confidence: 99%
“…Sanchez-Rola et al [50] showed a method relying on computer internal clock imperfections to fingerprint unique machines. Schwarz et al [51] presented JavaScript template attacks to create fingerprints and retrieved the instruction-set architecture and the used memory allocator.…”
Section: Hardware-based Side-channel Attacksmentioning
confidence: 99%
“…In addition to /proc file system data, and unprivileged API calls, side-channels may be formed by the methods exposed to unprivileged browser JavaScript. In [17], the authors perform a statistical analysis on these browser properties and demonstrate the detection of the; underlying operating system, CPU architecture, privacy-enhancing browser extensions, and exact browser version.…”
Section: Related Workmentioning
confidence: 99%
“…Rule-based web bot detection techniques that use browser fingerprints include font detection, plugin enumeration, WebGL fingerprinting, examination of unique to browser automation software strings in JavaScript variables, and more [5,23,31]. Furthermore, more advanced fingerprinting techniques have been proposed that can extract low level properties, such as the instruction-set architecture, and the used memory allocator [31]. However, research has shown that current commercial tools that detect web bots based on their fingerprint present several flaws [5].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Such web bots can crawl web servers in a humanlike manner to collect information making them harder to detect. Additionally, we can assume that the malicious web bots exhibit a fingerprint that is indistinguishable from that of a browser as in the opposite case, such bots could be deterministically detected using advanced fingerprinting techniques [5,22,23,31]. This is a logical assumption, as the respective Indicators of Compromise have a low pain threshold (i.e., they require low effort to be changed) [8].…”
Section: Threat Modelmentioning
confidence: 99%